Reliability of a Modular Standby Redundant System with Unrecoverable Failures - Arora, J. R. (Defence Science Journal, 2014)
This paper considers a stand by redundant system consisting of two identical modules. Each module is compose of N distinct components in series. The failure of a module may be attributed due to the failure of any of its N components. The ith components of a module has an arbitrary repair time CDF, G./sub i/ (t). The stand by module has been assumed to have a nonzero hazard rate even when unpowered. The failure of an on-line module is identified through a sensing device which has a probability 'c' of successfully recovering a fault in the on-line module. Expressions for the distribution of the Time to First System Failure (TFSF), the expected TFSF, and the reliability of the system have been derived by using the theory of Markov renewal processes.